Student Academic Committees: An Approach to Obtain Students’ Feedback - Samarasekera, Dujeepa; Karunathilake, I.M.; Dias, Ranjan (My University, 2006)
In 1995, the Colombo Medical Faculty changed its curriculum from a traditional model to an integrated one. The major challenge to the Faculty was obtaining students’ feedback on their learning activities. To overcome this, a new method where staff and student groups from different years of study engage in an interactive discussion relating to their learning environment was developed. This feedback was then processed and forwarded to the relevant authorities for necessary action.